The Behavior of Organizational Citizenship an Analytical Study - Kaouane, Mohamed; Benaidja, Mohamed (Journal of Human Sciences, 2021)
This research paper deals with one of the organizational variables, which is the organizational citizenship behaviors that represent the worker taking additional roles outside the job description and for which no reward is expected, and of course they are behaviors that make organizations achieve their goals and are positively reflected on the organizational and human levels.